2022
DOI: 10.1021/acschemneuro.2c00224
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Inhibitory Mechanism of the αB-Crystallin Domain against Aβ42 Aggregation and Its Effect on Aβ42 Protofibrils: A Molecular Dynamics Simulation Study

Abstract: Alzheimer′s disease (AD) is related to the misfolding and aggregation of amyloid-β (Aβ) protein, and its major pathological hallmark is fibrillary β-amyloid plaques. Impeding the formation of Aβ β-structure-rich aggregates and dissociating Aβ fibrils are considered potent strategies to suppress the onset and progression of AD. As a molecular chaperone, human αB-crystallin has received extensive attention in the inhibition of protein aggregation. Previous experiments reported that the structured core region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…With the β-sheet edges of Aβ monomers, oligomers, and proto-fibrils occupied by the highly charged SEVI, the corresponding growth to higher-molecular-weight oligomers, nucleation of proto-fibrils, and rapid fibril elongation could be inhibited. It is worth noting that the capping strategy to prevent edge-to-edge aggregation has been observed not only with SEVI but also with other amyloid inhibitors. , For instance, αB-crystallin has been found to inhibit Aβ aggregation by capping the β-sheet elongation edge. , Furthermore, a similar “negative design” approach that involves strategically positioning charged residues at the β-sheet edges has also been used in the design of amyloid inhibitors. , Mechanistic insights obtained from our systematic computational studies may aid in the development of novel therapeutic strategies to modulate the pathological aggregation of amyloid protein in degenerative diseases.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…With the β-sheet edges of Aβ monomers, oligomers, and proto-fibrils occupied by the highly charged SEVI, the corresponding growth to higher-molecular-weight oligomers, nucleation of proto-fibrils, and rapid fibril elongation could be inhibited. It is worth noting that the capping strategy to prevent edge-to-edge aggregation has been observed not only with SEVI but also with other amyloid inhibitors. , For instance, αB-crystallin has been found to inhibit Aβ aggregation by capping the β-sheet elongation edge. , Furthermore, a similar “negative design” approach that involves strategically positioning charged residues at the β-sheet edges has also been used in the design of amyloid inhibitors. , Mechanistic insights obtained from our systematic computational studies may aid in the development of novel therapeutic strategies to modulate the pathological aggregation of amyloid protein in degenerative diseases.…”
Section: Discussionmentioning
confidence: 86%
“…32,33 For instance, αB-crystallin has been found to inhibit Aβ aggregation by capping the β-sheet elongation edge. 34,84 Furthermore, a similar "negative design" approach that involves strategically positioning charged residues at the βsheet edges has also been used in the design of amyloid inhibitors. 85,86 Mechanistic insights obtained from our systematic computational studies may aid in the development of novel therapeutic strategies to modulate the pathological aggregation of amyloid protein in degenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Dominant Binding Sites and Interactions of EGCG on the CTE-Related R3-R4 Tau Dimer. Recent studies 61,62 indicate that the atomic contact number can well reflect the binding preference of the ligand on the amyloid protein. Therefore, we calculated the MC/side chain (SC) contact number and H-bond number between EGCG and the dimer to identify the dominant binding sites of EGCG on the CTErelated R3-R4 tau dimer.…”
Section: Egcg Induces Loosely Packed Conformations and Inhibits The I...mentioning
confidence: 99%
“…However, due to available experimental technologies, it is still challenging to systematically visualize the structure and self-assembly process of Aβ42 peptides under various conditions. Molecular simulations, on the contrary, may offer some useful information from the microscopic view, which have been extensively employed in this field. For example, Fatafta et al performed microsecond-scale molecular dynamics (MD) simulations to explore the dynamic behavior of the Aβ42 dimer in different environments and found that the secondary structure of the Aβ42 dimer exhibited a transition from a random coil to a β-sheet in solution, but it was inhibited to some extent in the presence of lipid bilayers. Man et al reported an all-atom MD simulation study on Aβ42 dimers, trimers, and tetramers.…”
Section: Introductionmentioning
confidence: 99%